Assessors in The South Sulawesi Provincial Level Vocational School Student Competency Competition (LKS) - Akbar Iskandar (Jurnal Abdimas Cendekiawan Indonesia, 2024)
Vocational education has a very important role in preparing the young generation to enter the world of work. Student Competency Competitions (LKS) are one way to test and improve students' skills at the vocational high school (SMK) level. This article discusses the experience and impact of participating as a judge in the South Sulawesi provincial-level vocational school worksheet. This in-depth review aims to convey a better understanding of the importance of the role of juries in improving the quality of vocational education in Indonesia. This activity not only provides valuable experience for students, but also provides insight to education administrators about the strengths and weaknesses of the curriculum and the learning methods applied. Through observations and assessments made during LKS, judges and organizers can identify areas that need improvement in the curriculum and teaching approach. The results of the LKS can be important input for developing more relevant and effective educational programs. Overall, vocational education through vocational schools and extracurricular activities such as LKS are strategic steps in preparing Indonesia's young generation to face the challenges of the world of work. By prioritizing the development of practical skills and involving various stakeholders, the vocational education system in Indonesia can continue to develop and produce a competent and high-quality workforce.